2007
DOI: 10.1016/j.neuron.2006.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Neural Predictors of Purchases

Abstract: Microeconomic theory maintains that purchases are driven by a combination of consumer preference and price. Using event-related fMRI, we investigated how people weigh these factors to make purchasing decisions. Consistent with neuroimaging evidence suggesting that distinct circuits anticipate gain and loss, product preference activated the nucleus accumbens (NAcc), while excessive prices activated the insula and deactivated the mesial prefrontal cortex (MPFC) prior to the purchase decision. Activity from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

68
779
7
38

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 991 publications
(892 citation statements)
references
References 38 publications
68
779
7
38
Order By: Relevance
“…3a). The SEM was based on known anatomical connections between the OFC and NACC and their relationships to subjective likability and purchase decisions (Chib, Rangel, Shimojo, & O'Doherty, 2009;Knutson, et al, 2007;Montague & Berns, 2002;O'Doherty, Kringelbach, Rolls, Hornak, & Andrews, 2001;Plassmann et al, 2007;Rolls, 2000). Consistent with this literature, the average song likability had significant path coefficients to both the OFC and NACC, and because of the direct connection between OFC and NACC, this path was also significant.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…3a). The SEM was based on known anatomical connections between the OFC and NACC and their relationships to subjective likability and purchase decisions (Chib, Rangel, Shimojo, & O'Doherty, 2009;Knutson, et al, 2007;Montague & Berns, 2002;O'Doherty, Kringelbach, Rolls, Hornak, & Andrews, 2001;Plassmann et al, 2007;Rolls, 2000). Consistent with this literature, the average song likability had significant path coefficients to both the OFC and NACC, and because of the direct connection between OFC and NACC, this path was also significant.…”
Section: Resultsmentioning
confidence: 65%
“…More recently, however, the widespread use of neuroimaging has raised the possibility of using functional magnetic resonance imaging (fMRI) in the marketing process (Ariely & Berns, 2010). Neuroeconomic research suggests that activity in reward-related regions of the brain, notably the orbitofrontal cortex and ventral striatum is predictive of future purchasing decisions of the individuals who are scanned (Hare, O'Doherty, Camerer, Schultz, & Rangel, 2008;Knutson, Rick, Wimmer, Prelec, & Loewenstein, 2007;Plassmann, O'Doherty, & Rangel, 2007;Plassmann, O'Doherty, Shiv, & Rangel, 2008). For neuroimaging to be useful in either a marketing or branding application, however, these neural signals would need to generalize to a larger group of individuals who themselves were not the direct object of brain scanning.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, inequitable decision making was accompanied by engagement of the AI, a region previously associated with subjective disutility (29). AI activity in this context cannot be ascribed to being self-serving (which also occurred during selfserving/equitable trials) or to being offered less money than the receiver (which also occurred during generous/equitable trials) but likely represented a response to inequity itself.…”
Section: Discussionmentioning
confidence: 80%
“…Recent approaches of utilizing fMRI data to predict an individual's choices have met with varying success rates. In general, approaches that utilize distributed patterns of activation do better than approaches relying on individual brain regions (Hampton and O'Doherty, 2007;Knutson et al, 2007;LaConte et al, 2006). The results of the regression analysis of our choice data indicate that there is a strong relationship between passively evoked activations and subsequent decisions about the same stimuli.…”
Section: Discussionmentioning
confidence: 85%
“…Choice may be subject to a stochastic process, such as an error in evaluating the payoffs of the available alternatives, which is not present during passive experience (Luce, 1959). Although recent studies have used brain activation to predict decisions (Hampton and O'Doherty, 2007;Knutson et al, 2007), these studies have relied on activation during the choice itself, and may therefore be subject to a similar stochastic component. This would explain why our results have a higher predictive power using passive activations than other studies have found using activation during decision making.…”
Section: Discussionmentioning
confidence: 99%